Vascular endothelial dysfunction in sickle cell disease by brachial artery flow mediated dilatation - Pranav Kumar Raghuwanshi (Asian Journal of Medical Sciences, 2014)
Objective: The present study was conducted aiming to assess endothelial function in sickle cell disease (SS), sickle cell trait(SA) and compare to endothelial dysfunction between sickle cell anemia (SS), sickle cell trait (SA) cases and control (AA) patients to evaluate correlation of endothelial dysfunction.